A Large-Scale European Union Study of Aircrew Fatigue During Long Night and Disruptive Duties - Dijk, H. van; Maij, A.; Sallinen, M.; Aeschbach, D.; Akerstedt, T. (Aerospace Medical Association, 2020)
We examined aircrew fatigue during the following flight duty periods (FDPs) mentioned in the European Union (EU) Flight Time Limitations (FTLs): night FDPs longer than 10 h and FDPs typical of disruptive schedules (early starts, late finishes, and nights). An alternative way of classifying night FDPs was also examined to reveal possible subcategories that warrant special attention.
Keywords: Human factors / man-machine interaction